An Analysis of Factors Affecting Labor Productivity of Upper Structure Work on the Hurun Beach Resort Project Using the AHP (Analytic Hierarchy Process) - Muhammad Yurizal (Journal of Engineering and Scientific Research, 2023)
Development and project development in Indonesia is very important and is expected to have a good impact on the economy of this country. To achieve reliable development, it is necessary to manage human resources with the aim of increasing construction productivity. The factor influencing productivity is one of the benchmarks for the success of construction development implementation. This study aims to analyze the factors and occupations that have a relative effect on labor productivity in the Hurun Beach Resort Project. The AHP method is the research method used to carry out the analysis in this study. This is because decision-making criteria and alternatives become a reference to obtain achievements so that the percentage of the desired productivity factor can be known. Based on the results of the sub-criteria analysis, the relatively influential factor is the shop drawing with a weight of 0.19432, the second is the experience factor of 0.11948, and the third is the factor of adding working hours 0.10936. After analyzing the sub-criteria and then getting the final weight, the alternative superstructure work that is relatively influential is formwork work with a weight of 0.03413, the second is ironwork 0.03049, and the third is casting work 0, 0207.